Left and right populism compared: The British case. (May 2017) - March, Luke
This article represents one of the few systematic comparisons of left-wing populism with other populisms. Focussing on the manifestos of six British parties in 1999–2015, the findings confirm that left-wing populists are more socio-economically focussed, more inclusionary but less populist than right-wing populists. The article makes four main substantive contributions. First, empirically, it shows that the much-touted populist Zeitgeist in the United Kingdom barely exists. Second, methodologically, it provides a nuanced disaggregated populism scale that has advantages over existing methods because it can effectively distinguish populist from non-populist parties and analyse degrees of populism. Third, theoretically, it shows that host ideology is more important than populism per se in explaining differences between left and right populisms. Fourth is a broader theoretical point: what is often called 'thin' or 'mainstream' populism' is not populism but demoticism (closeness to ordinary people). Therefore, analysts should not label parties 'populist' just because their rhetoric is demotic.